2021
DOI: 10.1007/s00167-020-06416-4
|View full text |Cite
|
Sign up to set email alerts
|

There are differences in knee stability based on lateral extra-articular augmentation technique alongside anterior cruciate ligament reconstruction

Abstract: PurposeThe purpose of the current study is to systematically review and network meta-analyze the current evidence in the literature to ascertain if there is a superior lateral extra-articular augmentation technique in conjunction with anterior cruciate ligament (ACL) reconstruction (ACL.R) with respect to knee stability, re-rupture rates and functional outcomes. Methods The literature search was performed based on the PRISMA guidelines. Cohort studies comparing ACL.R to ACL.R + lateral extra-articular augmenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 51 publications
(68 reference statements)
0
8
0
Order By: Relevance
“…Several biomechanical and clinical studies have shown that LET can improve both the kinematics and the clinical results when associated with an ACL reconstruction [16, 17, 20, 37, 55]. Nevertheless, few of them have evaluated the capacity of LET itself to modify the mechanics of an ACL‐deficient knee.…”
Section: Discussionmentioning
confidence: 99%
“…Several biomechanical and clinical studies have shown that LET can improve both the kinematics and the clinical results when associated with an ACL reconstruction [16, 17, 20, 37, 55]. Nevertheless, few of them have evaluated the capacity of LET itself to modify the mechanics of an ACL‐deficient knee.…”
Section: Discussionmentioning
confidence: 99%
“…Recent publications have shown the benefits of ALL reconstruction in achieving knee stability as well as reducing the iterative rupture rate. [13][14][15] Considering the high rerupture rate in the pediatric population, 6,7 reconstruction of both the ACL and ALL appears essential to us. To conclude, the described technique of combined ACL and ALL ligament reconstruction can be…”
Section: Discussionmentioning
confidence: 99%
“…The first main feature of the current ITB tenodesis is that we fix the anterior half of the ITB instead of the middle part of the ITB for modified Lemaire and other procedures PROCEDURE FOR ACL RECONSTRUCTION e5 because the route of the anterior part of the ITB is more like that of the native ACL. 10 The second main feature of current ITB tenodesis is that the ITB string is used to reconstruct the ACL, although the ITB strip is not so thick.…”
Section: Discussionmentioning
confidence: 99%